Cerebral Hypoxia: Its Role in Age-Related Chronic and Acute Cognitive Dysfunction. (29th March 2021) - Snyder, Brina; Simone, Stephanie M.; Giovannetti, Tania; Floyd, Thomas F.
Abstract : Postoperative cognitive dysfunction (POCD) has been reported with widely varying frequency but appears to be strongly associated with aging. Outside of the surgical arena, chronic and acute cerebral hypoxia may exist as a result of respiratory, cardiovascular, or anemic conditions. Hypoxia has been extensively implicated in cognitive impairment. Furthermore, disease states associated with hypoxia both accompany and progress with aging. Perioperative cerebral hypoxia is likely underdiagnosed, and its contribution to POCD is underappreciated. Herein, we discuss the various disease processes and forms in which hypoxia may contribute to POCD. Furthermore, we outline hypoxia-related mechanisms, such as hypoxia-inducible factor activation, cerebral ischemia, cerebrovascular reserve, excitotoxicity, and neuroinflammation, which may contribute to cognitive impairment and how these mechanisms interact with aging. Finally, we discuss opportunities to prevent and manage POCD related to hypoxia.